Guy Debord e a nova fase do espetáculo - Bueno, Douglas Aparecido (2017)
The thesis deals with the spectacle of Guy Debord theory under the aegis of its artistic, political and philosophical influences, putting in relief their main contributions to the analysis and overcoming of the spectacle. The spectacle, to Debord, is a relationship alienated for social and historical construction, which overcomes the media criticism, as is commonly assumed. The thesis reveals that the theory of the spectacle, in its origin, is a philosophical reflection on the story time, and in the light of hermeneutics interprets own theory on that basis. Analyze the theory of the spectacle, from the standpoint of time and story ideas, it offers a way to resolve the hegelian marxism of Guy Debord. The hegelian marxism Debord connects, in theory, its theoretical and philosophical interests in the concepts of strategy, chance and play, from the existential principles and based on these issues, investigates and theorizes the practice, political action in time and social history as a means to overcome the spectacle, or give you a new phase. Furthermore, to the extent that delimits the theory of this epistemological framework, it is apparent deficiencies. The theory of the spectacle is based on the unified separation of the actions of the subject (historical and social) and social interpretation under the same heading, which in turn replaces the Marxian analysis of capital as an antagonistic social relationship rather than the abstract opposition between homogenized and alienated consciousness of history and the world. Although this aspect apparently theoretical problem is, the notions of subjectivity, time and history significant role for social analysis. Putting in relief the Guy Debord’s position that all social action and every theory must be considered as strategic interventions, and that every theory must be an invitation to overcome them, the thesis takes up the hegelian marxism Debord to suggest spectacle that the theory is a sui generis moment within a historical action design. This means that all Debord’s theory provides a collective political will model and suggests a reflection on the possibility of this hermeneutic be developed